Engagement and Wellbeing: How sustainable behaviour is influencing our wellbeing - Omann, Ines; Mock, Mirijam; Lauer, Paul; Schuler, Julia (Momentum Quarterly, 2017)
Voluntary engagement generally influences the wellbeing of the practitioners and ideally leads to a positive cycle (doing well by doing good, cf. OECD 2015). However, this is more complicated when it comes to volunteering in the field of sustainability. Those who are involved in initiatives such as energy cooperatives, ecovillages or repair cafés are confronted with emotional challenges. Challenging aspects can be overstraining initiated through the excessive demand of time or the size of the problems such as climate change, as it might seem that one’s engagement does not lead to a notable contribution. Irrespectively of the challenges, engagement for sustainability can be perceived as a source of meaning and motivation and can lead to numerous positive effects on the own hedonistic and eudaimonic wellbeing. This paper shows the positive and negative impacts on the wellbeing of volunteers and discusses strategies to address the mentioned challenges. It is based on 39 in-depth interviews with people who are actively engaged in a variety of sustainability initiatives.
Keywords: voluntary engagement; sustainability initiatives; wellbeing; eudaimonic wellbeing; hedonic wellbeing